Study of Variability in the Cultivated Clones of Populus nigra Linn. (Black Poplar) of Kashmir Valley - Gangoo, S. A.; Mir, Mushtaq A.; Khan, A. A.; Zaffar, Gul (Indian Forester, 2011)
Screening of promising clones of Populus nigra Linn. (Black poplar) was carried out in Faculty of Forestry, SKUAST-K, J&K, India, during year 2006-07, to locate interclonal variation for various morphometric traits and to select best clones. A detailed survey was carried out in all the six districts of Kashmir valley from October, 2006 onwards and clones retaining leaves till late autumn were selected and tagged. Selected clones were evaluated for growth characteristics like progressive height, progressive collar diameter, monthly height increment, monthly diameter increment, number of leaves/plant, number of roots per plant, sprouting, survival, sprouting commencement days, leaf area. leaf breadth, and branch angle. Heritability and coefficient of variation were estimated through proper statistical procedure. Investigation revealed that significant interclonal variation exits for all these characters. Maximum loading (0.48) was found for height, followed by number of leaves (0.44), while minimum loading (0.31) was found for leaf area, accordingly height contributed maximum (30%), while leaf area contributed minimum (3%) to total variance. The ranking of clones was done on the basis of principal component score, which ranged from -5.17 (A, worst clone) to 5.48 (A, best clone). Heritability ranged from 60.13 per cent (minimum) for collar diameter to 93.05 per cent (maximum) for branch angle. Genetic advance ranged from a maximum of 29.24 for height to a minimum of 9.72 for branch angle.